Potato cultivar identification using molecular markers - Rosa, Patricia Marchezi; de Campos, Tatiana; de Sousa, Adna Cristina Barbosa; Sforça, Danilo Augusto; Torres, Gisele Abigail Montan; de Souza, Anete Pereira (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate a set of microsatellite markers for varietal identification and characterization of the most widespread potato cultivars in Brazil. The DNA from 14 potato cultivars was genotyped using microsatellite markers and the alleles were scored in silver-stained polyacrylamide gel. Twenty-four microsatellite markers were evaluated, and only one locus was monomorphic. Based on band patterns, a set of two microsatellites that were able to identify and differentiate all examined cultivars was obtained.